Selected fermented indigenous vegetables and fruits from Malaysia as potential sources of natural probiotics for improving gut health - Olaide Olawunmi Ajibola; Raymond Thomas; Babatunde Femi Bakare (Food Science and Human Wellness)
In the Peninsular Malaysia and Northern Borneo island of Malaysia, various rich indigenous leafy vegetables and fruits grow and contribute to the nutritional and dietary values of the population. They have high water contents, thus, naturally vulnerable to rapid food spoilage. Food preservation and processing play a vital role in the inhibition of food pathogens in fruits and vegetables that are prevalent in Malaysia. Lactic acid fermentation is generally a local-based bioprocess, among the oldest form and well-known for food-processing techniques among indigenous people there. The long shelf life of fermented vegetables and fruits improves their nutritional values and antioxidant potentials. Fermented leaves and vegetables can be utilized as a potential source of probiotics as they are host for several lactic acid bacteria such as Lactobacillus confusus, Weissella paramesenteroides, Enterococcus faecalis, Lactobacillus plantarum, Lactobacillus buchneri, Lactobacillus paracasei, Lactobacillus pentosus, Pediococcus acidilactici, Pediococcus pentosaceus and Leuconostoc mesenteroides. These strains may be more viable in metabolic systems whereby they can contribute to a substantial increase in essential biologically active element than industrial starter cultures. This review is aimed to address some essential fermented fruits and vegetables in Malaysia and their remarkable reputations as a potential sources of natural probiotics.